Outcomes of Dome-Shaped Upper Tibial Osteotomy for Correction of Tibia Vara In Pediatric Age Group A Mid-Term Follow-Up Study: Hasil dari Osteotomi Tibialis Atas Berbentuk Kubah untuk Koreksi Tibia Vara pada Kelompok Usia Anak-Anak: Sebuah Studi Tindak Lanjut Jangka Menengah - Al-Khafaji, Aymen Subhi Abbas (Universitas Muhammadiyah Sidoarjo, 2024)
Aims: To evaluate the outcome of dome-shaped high tibial osteotomy at the end of 24 months of follow up postoperatively using knee society, function score and knee alignment (HKA angel). Patients and methods: A sample of 21 patients (31 knee joints) with bilateral or unilateral genu varum of different etiology that was operated on between 1st. July.2014 - 31st.Dec.2015 in Al-Wasity Teaching Hospital by dome shaped high tibial osteotomy for correction of varus status and followed up for 24 months post-operatively for assessment of outcome of surgery was included in this study. Results: The mean of corrected angel on immediate post-operative assessment was 11.3° ±2.9 SD valgus (range 5–15°). This angle decreased to 6.4°±2.8 SD valgus at 24 months with 4.9° Loss of correction. The mean angel of correction was decreased by 3.1 ° to 9 month and 1.8 degree from 9 month to 24 months of follow up, and this difference concerning angel changes with time was statistically significant (p=0.01).We had 4 patients with unilateral varus due to Blount's disease were under corrected. The outcome as assessed by the knee society and functional score was either excellent or good with all patient's even those who were under correction also showed improvement in these score. No significant complications reported. Highlights: Evaluate dome-shaped high tibial osteotomy outcomes over 24 months. Analyzed 31 knees with genu varum post-osteotomy in 21 patients. Significant correction achieved; excellent/good functional outcomes; minor complications reported. Keywords: genu varum, high tibial osteotomy, knee society score and faction score, HKA angle.